The adaptation of Fusarium culmorum to DMI Fungicides Is Mediated by Major Transcriptome Modifications in Response to Azole Fungicide, Including the Overexpression of a PDR Transporter (FcABC1) - Hellin, Pierre; King, Robert; Urban, Martin; Hammond-Kosack, Kim E.; Legrève, Anne (Frontiers in Microbiology, 2018)
Fusarium culmorum is a fungal pathogen causing economically important diseases on a variety of crops. Fungicides can be applied to control this species with triazoles being the most efficient molecules. F. culmorum strains resistant to these molecules have been reported, but the underlying resistance mechanisms remain unknown. In this study, a tebuconazole-adapted F. culmorum strain was developed with a level of fitness similar to its parental strain. The adapted strain showed cross-resistance to all demethylation inhibitors (DMIs), but not to other classes of fungicides tested. RNA-Seq analysis revealed high transcriptomic differences between the resistant strain and its parental strain after tebuconazole treatment. Among these changes, FcABC1 (FCUL_06717), a pleiotropic drug resistance transporter, had a 30-fold higher expression level upon tebuconazole treatment in the adapted strains as compared to the wild-type strain. The implication of this transporter in triazole resistance was subsequently confirmed in field strains harboring distinct levels of sensitivity to triazoles. FcABC1 is present in other species/genera, including F. graminearum in which it is known to be necessary for azole resistance. No difference in FcABC1 sequences, including the surrounding regions, were found when comparing the resistant strain to the wild-type strain. Fusarium culmorum is therefore capable to adapt to triazole pressure by overexpressing a drug resistance transporter when submitted to triazoles and the same mechanism is anticipated to occur in other species.